Study on vibration of U-shaped flexible jumpers - Donghai, H.E. (Taylor's University, 2020)
During a free standing hybrid riser (FSHR) operation, because of vessel movement, a disturbance load is transmitted to the rigid risers through the U-shaped flexible jumpers from the vessel. This disturbance significantly affects the stability and fatigue of the entire system. To determine the effect of this disturbance, the dynamic load transmission characteristics of the disturbance through U-shaped flexible jumpers must be studied. To fulfil this aim, a lumped-mass flexible pipeline dynamic model is built. At the same time, the Newton-Î² iterative method and the Houbolt difference formula is employed for the time domain discrete calculation. To proof the theoretical model, the calculating results are verified with finite element software simulation. The disturbance transmission characteristics via U-shaped flexible jumper are studied from two aspects: 1. The relationship between the input disturbance and the output load; 2. The linear superposition characteristic of the output load. It is found that the frequency characteristics of the output load are the same as the input disturbance. On the other hand, after the transmission of input disturbance through the flexible jumper, the oscillation frequency and the delay time of the output show a linear superposition characteristic, while the output load amplitude exhibits a nonlinear superposition phenomenon. These results provide a basis for predicting the dynamic characteristics of the output load only by analysing the characteristics of the input disturbance. Â© School of Engineering, Taylor's University